1996
DOI: 10.1074/jbc.271.31.18445
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein B Sequence Requirements for Hepatic Very Low Density Lipoprotein Assembly

Abstract: We studied the structural requirements of apolipoprotein (apo) B for assembly of very low density lipoproteins (VLDL) using rat hepatoma McA-RH7777 cells expressing human apoB (h-apoB). Recombinant h-apoB48, like endogenous rat apoB48 (r-apoB48), was secreted as VLDL in addition to high density lipoproteins (HDL) by transfected cells, indicating that the N-terminal 48% of apoB contains sequences sufficient for VLDL assembly. Truncation of the C terminus of h-apo-B48 to -B42 or -B37 had little effect on the abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 46 publications
3
45
0
Order By: Relevance
“…3). This is because the previously commonly used density ultracentrifugation technique, although satisfactory for revealing the two-step process for B48-VLDL assembly (4,7,33), does not allow detection of size changes in VLDL particles containing large apoB (i.e. B80 or B100).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). This is because the previously commonly used density ultracentrifugation technique, although satisfactory for revealing the two-step process for B48-VLDL assembly (4,7,33), does not allow detection of size changes in VLDL particles containing large apoB (i.e. B80 or B100).…”
Section: Resultsmentioning
confidence: 99%
“…The cells were homogenized using a ball-bearing homogenizer (20 passages) (33), and the postnuclear supernatant was obtained by centrifugation (10,000 ϫ g, 4°C, 10 min). Heavy microsomes were isolated from the postnuclear supernatant by centrifugation using a microcentrifuge (16,000 ϫ g, 4°C, 15 min), and subsequently the light microsomes and cytosol were separated by centrifugation using a Beckman TLA-100.4 rotor (400,000 ϫ g, 4°C, 16 min).…”
Section: Figmentioning
confidence: 99%
“…Both Leu 343 and Arg 463 residues are located within the predicted ␣-helical domain of apoB, which contains sequence elements shown to be important for proper folding of apoB, for the physical interaction between MTP and apoB, and for lipoprotein assembly. Transfection studies have suggested that apoB segments containing sequences lacking the ␤␣1 domain were unable to be secreted (13) or else secreted poorly (14). Mutational analysis has identified critical disulfide linkages within the ␤␣1 domain that are essential for efficient secretion of apoB and apoB-containing lipoproteins (15,16,18).…”
Section: Discussionmentioning
confidence: 99%
“…Transfection studies show that apoB segments lacking the ␤␣1 domain are either unable to be secreted (13) or poorly secreted (14). Mutagenesis experiments show that correct disulfide bond formation within the ␤␣1 domain is required for efficient secretion of apoB (15)(16)(17), and this requirement is independent of the lipidation state of apoB (18).…”
mentioning
confidence: 99%
“…The labeling medium was then removed, and growth medium (DMEM plus 10% FBS) was added. Cells and medium were collected at the various time points up to 4 h after the initial pulse and harvested as described by McLeod et al (23). ApoA-I was immunoprecipitated from the media and cell lysates with anti-human apoA-I antisera (Roche Molecular Biochemicals) and protein G-Sepharose (Amersham Pharmacia Biotech) and then subjected to 12% SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%